ABU YUSUF'S ECONOMIC THOUGHT: PRINCIPLES, METHODOLOGIES, AND RELEVANCE TO MODERN ISLAMIC ECONOMICS - Fatoni, Siti Nur (Al-Muamalat: Jurnal Ekonomi Syariah, 2022)
This study investigates Abu Yusuf's economic thought, the prevailing views among scholars during his era, and the relevance of these ideas in modern economic contexts. The focus is on understanding the structure and characteristics of his economic concepts, the methodologies employed to address economic challenges, and their applicability to current developments. Grounded in an economic school of thought that integrates Islamic principles into economic life, the study highlights the combination of moral values, economic theory, and historical perspectives. Islamic economics is described as a framework of principles derived from the Qur'an and Sunnah, adaptable to the needs of specific periods and contexts. A historical-descriptive method is employed to analyze contributions to Islamic economics without internal critique. The central discussion addresses systemic issues affecting lower-income groups, such as economic disparities and unequal wealth distribution. Proposed solutions emphasize reducing burdens on marginalized groups and narrowing economic gaps. The analysis underscores the role of state institutions as mechanisms for enabling effective economic interventions, fostering equity, and promoting inclusivity. These perspectives offer insights for addressing modern economic challenges and integrating ethical and equitable principles into economic systems.